2023
DOI: 10.3390/agriculture14010051
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Evaluations of and Attitudes towards New Genome Editing Techniques: An Italian Case Study

Simona Romeo Lironcurti,
Federica Demaria,
Raffaele D’Annolfo
et al.

Abstract: The ever-increasing development of assisted evolution technologies (AETs) in agriculture has boosted crop improvement. The commercialization of improved biotech crops can be promoted by modern gene editing instead of conventional genetic modification, which is a cheaper and faster approach that can help address future agriculture challenges, such as food security, environmental sustainability, and climate change. However, the use of these technologies is still sensitive and debated in many countries. Each regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Finally, "Can agroforestry contribute to food and livelihood security for Indonesia's smallholder farmers in the era of climate change?" is the research question investigated by Indonesian and Chinese researchers [12]. They found that research directly related to food security and the quantification of ecosystem services is still limited and needs further investigation.…”
mentioning
confidence: 99%
“…Finally, "Can agroforestry contribute to food and livelihood security for Indonesia's smallholder farmers in the era of climate change?" is the research question investigated by Indonesian and Chinese researchers [12]. They found that research directly related to food security and the quantification of ecosystem services is still limited and needs further investigation.…”
mentioning
confidence: 99%